Estimates for Eigenvalues of the Elliptic Operator in Divergence Form on Riemannian Manifolds - Shenyang Tan; Tiren Huang; Wenbin Zhang (Advances in Mathematical Physics)
We investigate the Dirichlet weighted eigenvalue problem of the elliptic operator in divergence form on compact Riemannian manifolds (M,g,e-ϕdv). We establish a Yang-type inequality of this problem. We also get universal inequalities for eigenvalues of elliptic operators in divergence form on compact domains of complete submanifolds admitting special functions which include the Hadamard manifolds with Ricci curvature bounded below and any complete manifolds admitting eigenmaps to a sphere.